2011
DOI: 10.1123/jsm.25.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sense of Community From the Athlete’s Perspective

Abstract: Sport programs are often charged with creating a sense of community (SOC), and it is thought that doing so will benefit participants on and off the field of play. Since SOC is specific to the setting (Hill, 1996) and most research has been conducted outside of sport, the literature has not yet fully demonstrated how and when SOC is created within a sport context. Utilizing a grounded theory and phenomenological approach, this study investigated the mechanisms for creating SOC within a sport setting. Twenty for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 25 publications
5
90
1
3
Order By: Relevance
“…Specifically, these results supported Pretty and McCarthy's (1991) and Warner and Dixon's (2011) research that suggested that gender differences likely exist in terms of how Competition impacted SOC. The fact that Competition varied by gender is likely a result of the socialization process.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Specifically, these results supported Pretty and McCarthy's (1991) and Warner and Dixon's (2011) research that suggested that gender differences likely exist in terms of how Competition impacted SOC. The fact that Competition varied by gender is likely a result of the socialization process.…”
Section: Discussionsupporting
confidence: 75%
“…In doing so, a trust and reciprocal commitment developed and a SOC was cultivated. This factor was not seen in Warner and Dixon's (2011) previous study with varsity athletes, indicating that there may be some critical difference in terms of how SOC develops within a peerdirected versus a more formalized coach-or administrator-directed model.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In particular, these managerial actions and organizational structures were also perceived by referees to be a barrier to their advancement. Warner and Dixon (2011) also noted in their study involving athletes that the offfield (i.e., off-court) factors such as these were also more salient than one might expect. This is further supported by previous research on coaches (e.g., Chelladurai & Ogasawara, 2003;Dixon & Warner, 2010;Kim & Cunningham, 2005).…”
Section: Insert Figure 1 About Herementioning
confidence: 96%